Tissue-Specific Roles of NKT Cells in Tumor Immunity - Terabe, Masaki; Berzofsky, Jay A. (Frontiers in Immunology, 2018)
NKT cells are an unusual population of T cells recognizing lipids presented by CD1d, a non-classical class-I-like molecule, rather than peptides presented by conventional MHC molecules. Type I NKT cells use a semi-invariant T cell receptor (TCR) and almost all recognize a common prototype lipid, -galactosylceramide (-GalCer). Type II NKT cells are any lipid-specific CD1d restricted T cells that use other receptors and generally don’t recognize -GalCer. They play important regulatory roles in immunity, including tumor immunity. In contrast to type I NKT cells that most have found to promote anti-tumor immunity, type II NKT cells suppress tumor immunity and the two subsets cross-regulate each other, forming a novel immunoregulatory axis. They also can promote other regulatory cells including Tregulatory cells and myeloid-derived suppressor cells (MDSCs), and can induce MDSCs to secrete TGF-, one of the most immunosuppressive cytokines known. In some tumors, both Tregs and type II NKT cells can suppress immunosurveillance, and the balance between these is determined by a type I NKT cell. We have also seen that regulation of tumor immunity can depend on the tissue microenvironment, so the same tumor in the same animal in different tissues may be regulated by different cells, such as type II NKT cells in the lung vs Treg cells in the skin. Also, the effector T cells that protect those sites when regulatory cell are removed do not always act between tissues even in the same animal. Thus, metastases may require different immunotherapy from primary tumors. Newly improved sulfatide-CD1d tetramers are starting to allow better characterization of the elusive type II NKT cells to better understand their function and control it to overcome immunosuppression.